Nigerias Fiscal Health: An Analysis of Budget Process, Systems and Trends [2014 – 2016] - Fatai, Adedoyin Festus; Cheol, Liu; Shahumeel, Ahmed; Moses, Gumede Iga; May, Kirabo H; Safae, Laghmari; Bakar, Said Hamad (International Journal of Asian Social Science, 2017)
Nigeria is an oil dependent economy which faced a lot of economic and political challenges between the periods under review, such as increased broad money supply, fall in the value of money market assets, decline in the unpaid FGN Bonds, unfavorable exchange rates, fall in oil prices, and the May 2015 general elections, amongst others. Nigeria’s fiscal stance was thus threatened, and it is in light of these that the paper, uses interactions between expenditure, revenue, debts, and deficits trends, to compute indices that capture its fiscal health. The study found that using compounded annual growth rates (CAGR), certain sectors with high CAGRs (Interior, Transport, Finance, Science & Technology, and Health) seemed to be prone to high fiscal mismanagement. Also, conservativeness in applying debt instruments are unavailable, and such measures are not tied to growth; revenue from increased taxation are not matched with requisite infrastructure; and debts are not adequately tied to capital projects, as established in Fiscal Responsibility Act. Amidst several, few recommendations are undoubtedly notable mainly; that overhead costs revealed in several line-items and are marked up should be eradicated; and huge recurrent expenditure, mainly personnel cost (about 75% of the total budget) mostly visible as remuneration “in kind” should be strictly removed from the line items and programmes at MDA level. Thus, Nigeria’s government should maintain expenditure ceilings; create solidified link between policy and budget; establish realistic fiscal targets and indicators; and allow more public participation in budget process.